Trace elements distribution in soil, pore water and groundwater in Buenos Aires, Argentina - Heredia, Olga Susana (2009)
The concentration of trace elements in soils, pore water and groundwater was determined in order to evaluate their distribution in the different environmental matrices and their transport through the unsaturated zone to groundwater in an area near Buenos Aires, Argentina. Exchangeable forms of trace elements are more useful than total element concentration in soils as indicative of groundwater pollution risk. Although the analysis of pore water is of utmost importance for the study of the vertical mobility of major ions as well as phosphate, occurrence of trace elements in pore water was not correlated with their presence either as exchangeable forms in soil profiles or in groundwater. Soil profiles of exchangeable Mn, Zn and Ni were determined in the different localities of Escobar county. For Mn, the general trend is to diminish with depth with a slight increase at 60 cm depth. Nevertheless, this element was detected in groundwater but not in pore water. Exchangeable Ni ranged from 0.085 to 0.16 μg g- 1, with an increase in depth for the three evaluated soils. Zn was detected in all systems: soil, pore water and groundwater. Arsenic is of natural occurrence in groundwater. The concentration of the trace elements found in groundwater (Cu, Fe, Mn, Zn, V) are much higher in the shallow aquifer, which is more polluted due to anthropic activities.